Effect of an Integrated Complementary Childbirth Care Model on Neonatal Outcomes Care: A Quasi Experimental Study - Siti Mutoharoh; Dyah Puji Astuti; Sumarni Sumarni (An Idea Health Journal, 2026)
Background: Neonatal outcomes are key indicators of the quality of childbirth services and newborn adaptation. Complementary childbirth approaches, including hypnobirthing relaxation techniques, murottal therapy, and rebozo techniques, have been shown to enhance maternal comfort and facilitate a physiological labor process. The present study analyzed the effect of a complementary childbirth service model on neonatal outcomes. Methods: A quasi-experimental posttest-only control group design was employed, involving 60 women in labor (30 per group) recruited through purposive sampling without randomization. The intervention group received integrated complementary childbirth care, whereas the control group received standard care. Neonatal outcomes assessed included initial newborn assessment, APGAR score, blood glucose level within the first 24 hours after birth, and neonatal temperature status. Categorical outcomes were analyzed using Fisher's exact test, and the intervention effect was estimated using risk ratio (RR) with a 95% confidence interval (CI) (α = 0.05). Result: No significant differences were observed in initial newborn assessment, APGAR scores, or blood glucose levels between groups (all p = 1.000). However, neonatal vital signs differed significantly (p = 0.005), with the intervention group exhibiting a lower incidence of hypothermia (50.0% vs. 86.7%; RR = 0.58, 95% CI: 0.35). Conclusion:The integrated complementary childbirth care model was associated with improved neonatal temperature regulation, specifically a reduced incidence of hypothermia. These findings should be interpreted with caution due to the purposive sampling, non-randomized allocation, and posttest-only study design.